Indo‐Pacific origins of silky shark fins in major shark fin markets highlights supply chains and management bodies key for conservation - Cardeñosa, Diego; Fields, Andrew T.; Babcock, Elizabeth; Shea, Stanley K. H.; Feldheim, Kevin A.; Kraft, Derek W.; Hutchinson, Melanie; Herrera, Maria A.; Caballero, Susana; Chapman, Demian D. (Conservation letters, 2021)
The silky shark is the second most common shark in Southeast Asia's dried fin markets and is managed in the Atlantic Ocean by the International Commission for the Conservation of Atlantic Tuna (ICCAT) and by three Indo‐Pacific regional fisheries management organizations (RMFOs). The International Commission for the Conservation of Atlantic Tuna reports ∼ 7% of global silky landings but there is a moratorium on the export of their fins. During a 4‐year period (2014–2017) we used genetic differentiation observed between Atlantic and Indo‐Pacific silky sharks to assess the contribution of Atlantic individuals to fins randomly obtained in the two largest shark fin markets in the world, Hong Kong and Guangzhou, China (N = 604). We did not detect any Atlantic fins in either market despite robust sampling effort with an estimated Indo‐Pacific contribution of 99.8% to these markets. These findings indicate that supply chains for silky shark fins in Hong Kong and Guangzhou primarily originate in the Indo‐Pacific and are mainly under the purview of three Regional Fisheries Management Organizations. Our results are consistent with the possibility that ICCAT parties have achieved high compliance with the ban on silky sharks. We suggest research and monitoring improvements that could enhance our understanding of the global trade of silky sharks and enable better fisheries management.